Enhancement Legal Effectiveness of Handling and Prevention Processes Domestic Violence in Samarinda Through Empowerment PKK Group (Empowerment Well-being Family) - Tiyo Saputra; Khristyawan Wisnu Wardana; Agustina Wati (International Journal of Law, Crime and Justice, 2024)
Samarinda City is one of the cities located in East Kalimantan Province and is often found to have cases of Domestic Violence. The implementation of Law Number 23 of 2004 concerning the Elimination of Domestic Violence should be a solution to participate in preventing and overcoming acts of Domestic Violence as a law enforcement effort. However, in its implementation it turns out that there are still cases of Domestic Violence. The research approach used in this research is a Social Legal Research approach which aims to examine two main points of discussion, first to examine the handling of victims of Domestic Violence in Samarinda City. Second, to examine the role of the Perempuan Academy program in empowering community groups for Family Welfare Empowerment to prevent Domestic Violence in Samarinda City. The results of the research show that the handling of Domestic Violence in the City of Samarinda is provided both repressively and preventively, not only to deal with it after it occurs and is experienced by the victim, but also to participate in preventing it before the crime occurs in order to reduce cases of Domestic Violence in the City Samarinda and the Women's Academy program is considered sufficient to help the Family Welfare Empowerment group in Karang Anyar Village, Samarinda City to prevent Domestic Violence.